A Critical Analysis of History of Islamic Economic Thought as Response to Schumpeter's Claim of 'Great Gap' Period (700-1200 AD) - Jamshed, Kazi; Chachi, Abdelkader; Bulut, Mehmet; Chachı, Abdelkader; Bulut, Mehmet (Islamic Cultural Centre, 2024)
This exploratory research paper attempts to provide a constructive argument to confirm or refute the Austro-American economist Schumpeter's thesis of "Great Gap" mentioned in his book The History of Economic Analysis in 1954. The aims of the paper are twofold. The major aim is to focus especially on the assessment of Schumpeter's "Great Gap" thesis in the historical connotation of economic thought. Secondly, the paper aims to produce enough evidence to prove or disapprove his claim by presenting Muslim scholars' contribution in the evolution of the economic thought in the gap period (700-1200 AD). This paper uses qualitative research design through narrative literature review analysis though which relevant literatures have been studied to explore whether Schumpeter's "Great Gap" was really a gap or not. The findings show ample historical evidence that refutes his thesis of "Great Gap" in economic thought because there were huge literatures found that gap period and most of the literatures have been done by Arab-Islamic scholars. Also, there is a presence of self-contradictory statement while demonstrating his thesis. The findings of this research are useful for historians and economists to rethink the history of economic thought in the Middle Ages and create a scope for further research studies.
Keywords: Economic Thought; Great Gap; Joseph Schumpeter; Middle Ages; Muslim Scholars